Means to an end: teleological bias in moral reasoning - Davenport, Eloise; Coley, John D. (Frontiers in Psychology, 2025)
No model to date has integrated findings from teleological explanation with findings from moral reasoning to explore an underlying mechanism of moral cognition. We hypothesize that a preference for teleology, whereby consequences are assumed to be intentional, can explain instances where adults make judgments that seemingly neglect to account for intent. Across two studies, we investigated whether manipulating teleological reasoning influences moral judgment. 291 participants were evaluated in a 2 × 2 experimental design to assess the effects of teleology priming on adults’ endorsement of teleological misconceptions and moral judgments. Results provide some evidence that teleological reasoning influences moral judgment, but the findings are limited, context-dependent, and suggest that teleology is unlikely to be a strong influence in the explanation of outcome-based moral judgments.